Main trends and patterns in Women’s Football Migration - Tiesler, Nina Clara, 1968- (2012)
Paper presented at the International conference “Globalization, Migration and Development: The role of Football from a transnational perspective,” at Maastricht University, co-organized by Sport Science Institute of the University of Lausanne, 23 June 2011